Exploring helium ions' potential for post-mastectomy left-sided breast cancer radiotherapy - Bonaccorsi, Santa Gabriella; Tessonnier, Thomas; Hoeltgen, Line; Meixner, Eva; Harrabi, Semi B.; Hörner-Rieber, Juliane; Haberer, Thomas; Abdollahi, Amir; Debus, Jürgen; Mairani, Andrea (Cancers, 2024)
Simple Summary This research contributes to the ongoing scientific investigation of the benefits of particle therapy for left-sided breast cancer and presents the potential of the novel application of helium ion therapy. The results obtained reveal a significant improvement in target coverage for both proton and helium ion therapy compared to Volumetric Modulated Arc Therapy (VMAT). Furthermore, particle therapy leads to an increase sparing of surrounding healthy tissues, including the heart, the left anterior descending artery and the ipsilateral lung. Additionally, with the reduction of the low-dose exposure to the right side of the chest, the risk for secondary malignancies with particle therapy is potentially minimized compared to VMAT. Compared to proton therapy, helium could additionally reduce the risk of pneumonitis.Abstract Proton therapy presents a promising modality for treating left-sided breast cancer due to its unique dose distribution. Helium ions provide increased conformality thanks to a reduced lateral scattering. Consequently, the potential clinical benefit of both techniques was explored. An explorative treatment planning study involving ten patients, previously treated with VMAT (Volumetric Modulated Arc Therapy) for 50 Gy in 25 fractions for locally advanced, node-positive breast cancer, was carried out using proton pencil beam therapy with a fixed relative biological effectiveness (RBE) of 1.1 and helium therapy with a variable RBE described by the mMKM (modified microdosimetric kinetic model). Results indicated that target coverage was improved with particle therapy for both the clinical target volume and especially the internal mammary lymph nodes compared to VMAT. Median dose value analysis revealed that proton and helium plans provided lower dose on the left anterior descending artery (LAD), heart, lungs and right breast than VMAT. Notably, helium therapy exhibited improved ipsilateral lung sparing over protons. Employing NTCP models as available in the literature, helium therapy showed a lower probability of grade <= 2 radiation pneumonitis (22% for photons, 5% for protons and 2% for helium ions), while both proton and helium ions reduce the probability of major coronary events with respect to VMAT.
Gesehen am 11.11.2024